Marvel - absolutely everything you need to know ... ab - Bray, Adam; Cink, Lorraine; Sazaklis, John; Wilson, Sven (Dorling Kindersley Limited, 2016)
Packed with fun facts, bizarre-but-true tales, and quirky insights into everyone's favorite Marvel comic characters, including The Avengers, Spider-Man, and Daredevil. little-known facts and information about the iconic Marvel characters
Keywords: Marvel Comics Group / Miscellanea; Marvel Comics Group; Comic books, strips, etc / United States / Miscellanea; Comic strip characters / Miscellanea; Superheroes / Miscellanea; Comic books, strips, etc; Comic strip characters; Superheroes; JUVENILE NONFICTION / Media Tie-In; Held; United States; Bildband